Effects of body mass index and full body kinematics on tennis serve speed - Wong, F. K.; Keung, J. H.; Lau, N. M.; Ng, D. K.; Chung, J. W.; Chow, D. H. (Journal of Human Kinetics, 2014)
Effective training to improve serve speed is important for competitive tennis players. The purposes of this study were to investigate the effects of anthropometric factors and whole body kinematics of elite players on ball speed and to propose possible training strategies for improving the quality of tennis serves. Body and racket kinematics of tennis serves of 12 male elite Hong Kong players were investigated. The tennis serve was divided into four phases: I) Back-Swing Phase, II) Lead-Leg-Drive Phase, III) Forward-Swing Phase, and IV) Follow-Through Phase. It was shown that racket-side knee range of motion during phases II and III (r=0.705; p<0.05), racket-side knee peak extension velocity during phase II (r=0.751; p<0.01), racket-side hip peak extension velocity during phase II (r=0.657; p<0.05), racket-side shoulder range of motion in the coronal plane during phase III (r=0.616; p<0.05), racket-side elbow peak extension velocity during phase III (r=0.708; p<0.01) and body mass index (r=0.577; p<0.05) were significantly correlated with ball speed. Body mass index and the identified kinematic parameters that were significantly correlated with ball speed could be used as training guidelines for coaches and players to improve serve speed. Players should pay particular attention in training to increasing the extension velocity and range of motion of the identified joints.